The Implementation of Spectrophotometers in STEM-Based Physics Education: A Bibliometric Analysis - Fakhira Nursabrina; Bambang Heru Iswanto; Hadi Nasbey; Firmanul Catur Wibowo (Universitas Lambung Mangkurat, 2025)
The paucity of scientific research focusing on the integration of spectrophotometers within STEM-based physics education highlights a significant gap in the existing literature. This underexplored area holds considerable potential, as the application of spectrophotometric tools in instructional settings may enhance students’ scientific competencies and critical thinking skills. This study aims to address an unresolved research gap by conducting a comprehensive data analysis, combining various analytical techniques to obtain more accurate and comprehensive results regarding the implementation of spectrophotometry in STEM-based physics education. Bibliometric analysis was conducted on articles, conference papers, book chapters, and reviews. The research method used in this study combines quantitative analysis and descriptive methods. The results showed an annual growth rate of 29.24% with an average of 4,568 citations per document. China dominated journal publications with 71 articles, while Indonesia contributed 35 articles. This indicates that, especially in the realm of education, this topic is rarely explored in Indonesia. Data show that research on STEM and spectrophotometry continues to increase, except in 2022, when it experienced a significant decline, followed by a notable increase in 2024, compared to previous years, with 119 documents. Furthermore, WordCloud and co-occurrence network data indicate that STEM and spectrophotometry in physics education are under-researched topics. The topics most frequently researched in these articles are non-educational, such as spectrophotometry for humans, animals, or metabolism. This research recommends that the topic of spectrophotometry in STEM-based physics education should be further explored. Practically, these insights may serve as a foundation for educators and curriculum developers to begin incorporating laboratory tools, such as spectrophotometers, into physics instruction to foster 21st-century skills—particularly scientific literacy, problem-solving, and students' critical thinking abilities.